Data for RSF analysis of wolf - Courbin, Nicolas; Fortin, Daniel; Dussault, Christian; Courtois, R. (Dryad Digital Repository, 2014)
Data used to model the relative probability of occurrence of wolf in winter as a function of features of the networks of its prey (Tables 5 and 6). Network features are provided at observed GPS locations and at random locations.